2008
DOI: 10.1038/nbt.1510
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent chromosomal abnormalities in human embryonic stem cells

Abstract: Cultured human embryonic stem (hES) cells have a known predisposition to aneuploidy of chromosomes 12, 17 and X. We studied 17 hES cell lines by array-based comparative genomic hybridization (aCGH) and found that the cells accumulate other recurrent chromosomal abnormalities, including amplification at 20q11.21 and a derivative chromosome 18. These genomic changes have a variable impact at the transcriptional level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
158
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 229 publications
(175 citation statements)
references
References 13 publications
8
158
1
2
Order By: Relevance
“…32 De-novo aberrations in hESC lines have been previously reported, some of them shows very fast culture take over. 33 Here, we report high prevalence of aneuploidy in chromosomes 17 and 18, and although it is not statistically significant higher than other chromosomes, trisomy 17 aneuploidy is highly interesting as it was rarely reported in iPSCs. Significant difference was found in our research between monosomy and trisomy rate, suggesting that chromosome loss is more common.…”
Section: Aneuploidy Screeningmentioning
confidence: 51%
“…32 De-novo aberrations in hESC lines have been previously reported, some of them shows very fast culture take over. 33 Here, we report high prevalence of aneuploidy in chromosomes 17 and 18, and although it is not statistically significant higher than other chromosomes, trisomy 17 aneuploidy is highly interesting as it was rarely reported in iPSCs. Significant difference was found in our research between monosomy and trisomy rate, suggesting that chromosome loss is more common.…”
Section: Aneuploidy Screeningmentioning
confidence: 51%
“…All hESC lines were characterized using aCGH, initially using in-house arrays from the Nucleomics Core (VIB, K.U. Leuven) 20 and later using the 4 Â 44 K Human Genome array as described in the section below.…”
Section: Methodsmentioning
confidence: 99%
“…This might be particularly useful since S684 Review. Genetic evaluation of therapeutic hESC E. Stephenson et al hESCs in culture have been shown to acquire small chromosomal amplifications or deletions (Maitra et al 2005;Lefort et al 2008;Spits et al 2008;Hovatta et al 2010;Närvä et al 2010). UPD, a condition in which both alleles have originated from a single parent, occurs as heterodisomy and isodisomy (Engel 1980;Robinson 2000).…”
Section: Upd-a Form Of Lohmentioning
confidence: 99%